Pendampingan Praktik Mengajar Mahasiswa FKIP sebagai Upaya Peningkatan Mutu Proses Pembelajaran di Madrasah Aliyah Ulumuddin - Teuku Azhari; Juwita Sahputri; Rasyimah; Idaryani (Universitas Malikussaleh, 2026)
This community service program is entitled Mentoring of FKIP Student Teaching Practices as an Effort to Improve the Quality of the Learning Process at MA Ulumuddin. The goal is to strengthen the pedagogic competence of prospective teacher students and improve the quality of the learning process at partner schools. The implementation method is in the form of intensive assistance during Field Experience Practice (PPL) for 5 FKIP students at MA Ulumuddin, from September to December 2025. The mentoring model combines remote consultations via mobile phones, classroom monitoring visits, and rubric-based assessments. The results of the evaluation showed a significant improvement in student competence in preparing lesson plans, implementing interactive teaching strategies, managing classes, and conducting assessments. On the other hand, partner schools benefit in the form of refreshing pedagogical practices in the classroom. This program proves the effectiveness of the university-school partnership model that has a dual impact, namely preparing competent teacher candidates and at the same time contributing to improving the quality of education at the school level. For this reason, replication and institutionalization of this model are highly recommended for sustainability.